Realms of royalty : new directions in researching contemporary European monarchies - Jordan, Christina; Polland-Schmandt, Imke (Edition Kulturwissenschaft, 2020)
Monarchies are constantly adapting to the challenges of contemporary society - consequently, research on monarchies has to adapt as well. This collection introduces new directions in researching contemporary European monarchies by suggesting theoretical approaches to recent developments (e.g., pop concerts during royal celebrations) and new perspectives on royal families' interactions with their subjects (e.g., during royal tours). With its interdisciplinary analyses, the book is a timely answer to the renewed academic and popular interest in monarchies, providing a comprehensive understanding of European monarchies in their contemporary historical contexts.